2017
DOI: 10.1097/md.0000000000007658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a rational-emotive health education intervention on stress management and irrational beliefs among technical college teachers in Southeast Nigeria

Abstract: Background:Stress is the product of how an individual reacts and adapts to the specific demands and threats they encounter while carrying out given tasks. The main purpose of this study was to investigate the effects of a rational-emotive health education intervention (REHEI) on stress management, and irrational beliefs in a sample of technical college teachers in Southeast Nigeria.Method:The study design was a pretest–posttest control group. Repeated measures analysis of variance, paired t test and Mann–Whitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 31 publications
6
62
0
1
Order By: Relevance
“…6 The present results are also in accordance with a study that showed REEI was significantly effective in the stress management and irrational beliefs among college teachers in Nigeria. 5 In addition, our findings confirm other studies that have shown burnout symptoms primarily result from irrational beliefs. [6][7][8] Crucially, irrational beliefs can build maladaptive cognitive patterns which lead to professional burnout.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…6 The present results are also in accordance with a study that showed REEI was significantly effective in the stress management and irrational beliefs among college teachers in Nigeria. 5 In addition, our findings confirm other studies that have shown burnout symptoms primarily result from irrational beliefs. [6][7][8] Crucially, irrational beliefs can build maladaptive cognitive patterns which lead to professional burnout.…”
Section: Discussionsupporting
confidence: 90%
“…Therapeutic techniques such as relaxation, stretching, and cognitive restructuring exercises were used. 5,11 The REAEI program covered 32 therapeutic sessions each lasting two hours for 16 consecutive weeks (i.e., two sessions per week. Four similar follow-up sessions over two weeks occurred three months after the last therapy session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our review on REBT literature on Web of Science database found that out of REE literature published within 2006-2018, most of the applications of REE program were on HIV risk perceptions among in-school adolescents (Onyechi, Eseadi, Okere, & Otu, 2016), teachers' emotional distress (Bora et al, 2009;Ugwoke et al, 2017), school children (Cristea, Benga, & Opre, 2008;Opre, Buzgar, & Dumulescu, 2013;Trip et al, 2007), and teenagers from a high school (Lupu & Iftene, 2009). Critical discussion on the REE model development, especially for boarding school students' stress intervention, is found to be absent.…”
Section: Research-article20192019mentioning
confidence: 99%
“…For example, “students should not be frustrated”; “people who misbehave deserve severe punishment”;“there should be no discomfort or frustration at school”; and “teachers always need a great deal of help from others to solve school-related problems.” These irrational beliefs can lead to a wide range of psychological problems, including extreme stress. [ 45 , 49 51 ]…”
Section: Introductionmentioning
confidence: 99%